Tinjauan Filosofis Pembuatan Rumah Berdasarkan Adat Islam Jawa - Ainun Yudhistira (UIN Raden Mas Said Surakarta, 2018)
Javanese moslem traditions are to have many perspectives among moslem majority in Indonesia. There some traditions which are considered as deviating from Islamic laws. Meanwhile, some people want to guide that the tradition has a meaning associated in the Javanese moslem community such as Islamic architecture for houses. This study is going to elaborate Islamic architecture associated with Javanese traditions. It uses descriptive method to understanding the object. The results show that Javanese moslem community represents understanding Islam as metaphysical things; collaboration between Islam and Java generates an understanding behavior of human life; and Islamic architecture of javanese houses represents devinity and harmony.